Beyond Plot, Character, and Theme: Literary Discourse and Interpretive Procedures in ELA Education - LeBlanc, Robert Jean (Language and Literacy / Langue et littératie, 2025)
This essay explores the relative dominance of plot, character, and theme as core concepts in English Language Arts (ELA) and argues for a renewed focus on literary discourses and the teaching of interpretive procedures. Using Cormac McCarthy’s All the Pretty Horses as a case study, it illustrates how instructional attention to narrative style, point of view, and form can reveal and nurture the processes of literary meaning making and better align high school ELA with disciplinary practices of reading.